1999
DOI: 10.1017/s0007114599000215
|View full text |Cite
|
Sign up to set email alerts
|

The comparative roles of polyunsaturated fatty acids in pig neonatal development

Abstract: The present review focuses on the importance of polyunsaturated fatty acid (PUFA) provision for the normal development of the pig neonate. The review describes first the selected fatty acid composition of a range of porcine tissues including nervous tissues, muscle and adipose tissues, reproductive organs and immune-responsive organs and/or cells. The importance of PUFA to the functioning of the immune system of the neonate is considered briefly and is followed by an indepth consideration of the sources of PUF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
24
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(26 citation statements)
references
References 125 publications
2
24
0
Order By: Relevance
“…Omega-3 PUFA from fish oil have been shown to improve the development of the brain and immunity of neonatal piglets (Leskanich and Noble, 1999); however, there is little information regarding the effect of n-3 PUFA on fertility in sows. Palmer et al (1970) reported an increase in litter size born in first-and second-parity sows when diets containing fish meal were fed over the first 2 parities.…”
Section: Introductionmentioning
confidence: 99%
“…Omega-3 PUFA from fish oil have been shown to improve the development of the brain and immunity of neonatal piglets (Leskanich and Noble, 1999); however, there is little information regarding the effect of n-3 PUFA on fertility in sows. Palmer et al (1970) reported an increase in litter size born in first-and second-parity sows when diets containing fish meal were fed over the first 2 parities.…”
Section: Introductionmentioning
confidence: 99%
“…doi:10. 1016/j.livsci.2006.01.009 cardiovascular diseases) and are necessary in order to attain optimal pre-and post-natal growth (Leskanich and Noble, 1999;Williams, 2000;Simopoulos and Cleland, 2003;EFSA, 2005;MacRae et al, 2005). Increasing public awareness about the health benefits attributable to n-3 PUFA has stimulated interest in the sources of these fatty acids available for human consumption, also considering that western diets are rich in n-6 fatty acids and the overall consensus is that the n-6:n-3 ratio of diets should be reduced by increasing the intake of n-3 fatty acids (Department of Health, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…EFAs are fatty acids which are required by an organism for the maintenance of normal growth and reproduction, are not able to be synthesized by the organism, and are therefore required in appropriate amounts in the diet (Leskanich and Noble, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore dietary supplementation with fat to enhance energy and EFA supply during the late gestation and lactation may be an effective way of increasing the EFA content in piglet tissue and the EFA level of colostrum and milk, thereby improving the viability of piglets (Gu and Li, 2003) and the immune status of the neonate (Leskanich and Noble, 1999). Differences in placenta development may cause differences in piglet storage of glycogen (Wu et al, 2006).…”
Section: Introductionmentioning
confidence: 99%